2020
DOI: 10.1111/jan.14631
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with employment outcome after critical illness: Systematic review, meta‐analysis, and meta‐regression

Abstract: Review methods: Peer-reviewed articles that included adult ICU survivors and employment outcomes. Two investigators independently reviewed articles following the PRISMA protocol. Pooled prevalence for RTW was calculated. Meta-regression analyses were performed to assess the association between disability policies, temporal factors and RTW following ICU. Results: Twenty-eight studies (N = 8,168) met the inclusion criteria. All studies were scored as 'low risk of bias'. Using meta-analysis, the proportion (95% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The median severity of depression score was significantly higher in those with physical dysfunction than in those without physical dysfunction (8 [6-10] vs. 4 [2][3][4][5][6][7], p<0.01, respectively).…”
Section: Relationships Between Severity Of Depression and Physical Dy...mentioning
confidence: 99%
See 1 more Smart Citation
“…The median severity of depression score was significantly higher in those with physical dysfunction than in those without physical dysfunction (8 [6-10] vs. 4 [2][3][4][5][6][7], p<0.01, respectively).…”
Section: Relationships Between Severity Of Depression and Physical Dy...mentioning
confidence: 99%
“…National employment and disability policies could also contribute to the resumption of work productivity among those discharged from the ICU. Su et al [5] have revealed that the disability policies of each country were related to the resumption of work productivity. Thus, it is worth evaluating how those discharged from the ICU fare regarding employment in each country.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this this version posted December 2, 2021. ; https://doi.org/10.1101/2021.12.01.21266910 doi: medRxiv preprint Third, disability policy in each country should influence the proportion of employees returning to work among patients discharged from intensive care. A recent systematic review and meta-analysis using meta-regression revealed that disability policies in each country positively impacted the ability of ICU-discharged patients to return to work [3]. From OECD (Organization for Economic Co-operation and Development) data, the integration index that was calculated from ten criteria such as employment programs and governmentprovided job training was higher in Japan than the median index of OECD.…”
Section: Multivariable Analysismentioning
confidence: 99%
“…National employment and disability policies could contribute to resumption of work productivity among those discharged from the ICU. Su et al [3] revealed that the disability policies of each country were related to resumption of work productivity. Thus, it is worth evaluating how those discharged from the ICU fare in terms of employment in each country.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, previously employed survivors of ARDS who required intensive care commonly experience joblessness over 5-year followup (36%-68%). [2][3][4] Hence, a greater understanding of occupational and patient factors associated with post-ARDS employment outcomes is urgently needed. Among ARDS survivors, existing patient and hospitalization factors associated with joblessness include older age, non-White race, chronic health conditions, prolonged mechanical ventilation, and longer ICU and hospital lengths of stay.…”
mentioning
confidence: 99%